2020
DOI: 10.3390/ma14010155
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Mortars Reinforced with Amazon Rainforest Natural Fibers

Abstract: The addition of natural fibers used as reinforcement has great appeal in the construction materials industry since natural fibers are cheaper, biodegradable, and easily available. In this work, we analyzed the feasibility of using the fibers of piassava, tucum palm, razor grass, and jute from the Amazon rainforest as reinforcement in mortars, exploiting the mechanical properties of compressive and flexural strength of samples with 1.5%, 3.0%, and 4.5% mass addition of the composite binder (50% Portland cement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
(66 reference statements)
1
20
0
Order By: Relevance
“…This is, however, lower than the decrease in strength reported elsewhere [35], although with a higher fibers' content. A similar trend has been found in other papers concerning the modification of natural fibers [17,36,37]. The plot of the applied force vs. the midspan deflection for the reinforced 3 wt% samples is shown in Figure 7.…”
Section: Resultssupporting
confidence: 86%
“…This is, however, lower than the decrease in strength reported elsewhere [35], although with a higher fibers' content. A similar trend has been found in other papers concerning the modification of natural fibers [17,36,37]. The plot of the applied force vs. the midspan deflection for the reinforced 3 wt% samples is shown in Figure 7.…”
Section: Resultssupporting
confidence: 86%
“…Their results showed that treated fibers increased the performance of the composites during mechanical testing. It was further noticed that the inclusion of treated fibers above 3% increased the flexural strength than those without fibers [ 151 ]. A study on the mechanical properties of the jute-reinforced geopolymer composite was carried out by Sankar and Kriven.…”
Section: Geopolymers and Natural Fiber-reinforced Compositesmentioning
confidence: 99%
“…Recent studies report the mechanical properties, structural behavior, and possible applications of natural fibers in cementitious materials [ 14 , 31 , 32 , 47 ]. Several factors affect the properties of natural fiber-reinforced composites, such as the proportion of cellulose, as presented previously, the type of fiber used, fiber geometry, fiber structure, fiber surface (related to its adhesion and interface with the hue), mixing method, fiber dispersion (avoid fiber agglomeration, reduces the presence of voids and favors the interfacial bond with the matrix), fiber orientation (the alignment to a parallel direction contributes to a better viscosity of the matrix), matrix selection, interface strength (matrices of cementitious materials and natural fibers, which are limited due to the hydrophobic characteristic of natural fibers; however, treatments can improve the interface strength), manufacturing (temperature, pressure, and speed of processing of the fiber or composite), porosity, curing method, physical properties, cell dimensions, and microfibrillar angle [ 48 , 49 , 50 , 51 ].…”
Section: Properties and Importance Of Use In Cementitious Materialsmentioning
confidence: 99%
“…Regarding water absorption, da Fonseca et al [ 31 ] noted that compared to other fibers, such as tucum palm and jute, piassava fiber has the lowest water absorption. Regarding compressive strength, the piassava composite with 4.5% fiber had a slight increase in strength from 22.23 to 24.59 MPa [ 31 ].…”
Section: Properties and Importance Of Use In Cementitious Materialsmentioning
confidence: 99%